A new data‐driven riparian revegetation design method. Issue 8 (9th August 2021) - Bair, John H.; Loya, Sunny; Powell, Brian; Lee, James C.
Abstract: Hydrologic and physical gradients influence vegetation zonation and can form the basis of riparian revegetation design. We present a new data‐driven method to develop riparian revegetation designs by relating the ground height above river (HAR) or a low streamflow water surface as a groundwater proxy to existing vegetation cover types and applying those relationships to design conditions. Steps in the process are as follows: (1) map existing vegetation within the riparian corridor; (2) construct existing and design topographic and groundwater digital elevation models (DEMs), and then difference those DEMs to create a HAR detrended DEM (HAR dtDEM); (3) define existing vegetation habitat zones using the relationship between existing HAR dtDEM and mapped vegetation cover types; (4) apply habitat zone boundaries to detrended design topography; and (5) develop planting schematics using habitat zones and detrended design topography. We developed a revegetation design for a rehabilitation site on the Trinity River, California, using the HAR dtDEM method. We used a data‐driven method to define five habitat zones in riparian areas: aquatic, emergent margin, mesic, mesic–xeric transition, and xeric zones. Zonal boundaries were identified using four criteria: (1) capillary fringe elevation above the low flow water surface, (2) shifts from herbaceous to woody‐dominated cover types, (3) a difference equal to or >0.5 m between two adjacent ranked cover types, and (4) locations where a linear trendline intersected median HAR values or where a group of regression residuals changed from positive to negative or vice versa. The capillary fringe height was the most effective method when determining vegetation zones near the channel. The shift between herbaceous and woody‐dominated cover types defined the boundary between the emergent margin and mesic zone. Elevation increases >0.5 m between adjacent ranked cover types defined the upper and lower mesic–xeric transition zone boundaries best. Comparing linear residuals was most useful for separating drier cover types occurring on higher ground surfaces. Existing habitat zone boundaries were applied to detrended design topography to direct which selected native plant species could be arranged within habitat zones to improve planting survival and increase ecological function following rehabilitation.